Development of an immobilized biocatalyst with lipase and protease activities as a multipurpose cross-linked enzyme aggregate (multi-CLEA). Issue 12 (December 2015) - Mahmod, Safa Senan; Yusof, Faridah; Jami, Mohammed Saedi; Khanahmadi, Soofia; Shah, Harmen
Graphical abstract: Highlights: Multi-CLEA of protease and lipase activities was successfully prepared. Optimum preparation parameters of Multi-CLEA were determined using FCCCD under RSM. Multi-CLEA was recycled up to 5 cycles. Multi-CLEA showed higher stability than the free lipase and protease. Multi-CLEA successfully catalyzed two separate reactions. Abstract: This study focused on the production of a novel multi-CLEA comprising the enzyme activities of lipase and protease from fish viscera. A multi-CLEA is a single biocatalyst that can catalyze separate unrelated reactions, but these reactions can be conducted in one application. Tests pertaining to the effect of various additives on the multi-CLEA's activity were performed. Response Surface Methodology's Face Centered Central Composite Design (FCCCD) was employed to optimize the preparation parameters of the multi-CLEA in an aqueous medium. It was found that 55% (w/v) of ammonium sulfate, 65 mM of glutaraldehyde, and 0.113 mM of bovine serum albumin were the optimum levels of additives to prepare the multi-CLEA with the protease and lipase recovery activity of 43.82% and 99.91%, respectively. Multi-CLEAs were found to retain an average of more than 34% of the initial activity after five consecutive batches for both enzymes. Finally, the multi-CLEA was utilized to catalyze two reactions: improved washing process and biodiesel production. The stain removal percentage of a commercial detergent was improved by 67.78% after adding multi-CLEA. In addition, the multi-CLEA catalyzed biodiesel production from vegetable oil with a percentage conversion of 51.7%. Such results demonstrated that the multi-CLEA is a promising catalyst for biotechnological applications.